Practical psychometrics a guide for test users - Lovett, Benjamin J. (The Guilford Press, 2023)
"I wrote this book to fill a gap-to try to explain the basics of psychometrics to the people who need that understanding most: test users. Professionals such as school psychologists, special educators, counselors, speech-language pathologists, and social workers sometimes administer tests and scales, or review evaluation reports with test data, and need to make sense of the test scores that they see. The book's content is (a) accessible, (b) intuitive, (c) concise, (d) clinically relevant, and (e) technically accurate"-- Provided by publisher.